ON APPLICATION OF ACETYLAMINOSICCINE ACID IN NEUROPEDIATRICS - V.M. Studenikin; S.V. Balkanskaya; V.I. Shelkovskiy ("Paediatrician" Publishers LLC, 2008)
The article focuses on theoretical and practical aspects of using acetylaminosuccinic acid (cogitum) in neuropediatrics. General properties of amino acid drugs were discussed. Special attention was attributed to chemical and biophisiological features, metabolism and principles of activity in CNS of aspartic acid. Pharmacological properties of acetylaminosiccine acid, official indications for its use provided by manufacturers plus others (pathology according to icdb10), contraindications, adverse reactions, and peculiarities of dosage and treatment regimen were described.Key words: acetylaminosiccine acid, aspartic acid, children, neuropediatry, neurodietology.